Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm reading through my professor's class notes for Fourier Analysis and there is a remark that I can't verify.

He notes that:

$$[\sigma_n (f)](x) - f(x) = \frac1{2\pi}\int_{-\pi}^\pi [f(x+t) - f(x)]K_n(t)\;\mathrm dt.$$

Note that here $K_n$ is the Fejer kernel of $f$, and the factor of $2\pi$ comes from the fact that we scaled the $L_1$ norm by this factor which I have noticed is not always done.

I tried using the fact that $\sigma_n (f)$ is equal to $f*K_n$, which let me obtain:

$$[\sigma_n (f)](x) - f(x) = \frac1{2\pi}\int_{-\pi}^\pi f(x+t)K_n (t)\;\mathrm dt - f(x)$$

I can't see how to get the $K_{n}$ inside the integral, let alone attached to the factor of $K_{n}$. Thanks for the patience, I just am learning how to use this site. :)

Note that the definition of $\sigma_n (f)$ is $\frac1{n}\sum\limits_{j=0}^{n-1}S_j (f)$, where $S_j (f) = \sum\limits_{m=-k}^k\widehat{f}(m) e^{imt}$ is the $j$-th partial sum of the Fourier series of $f$.

share|improve this question
    
it's difficult to read. Put the formulas between two "$$" Can you add it in the question? –  Davide Giraudo Sep 30 '11 at 18:37
    
Ok. I put all my subsequent comments into the OP with proper formatting. Sorry I didn't realize I could edit my post at first. Now I seem to have the hang of inserting tex code too. Thank you. –  Kyle Schlitt Sep 30 '11 at 19:00
    
The Fejer Kernel is integrable, so you can write $f(x)=c\int_{-\pi}^{\pi}f(x)K_n(t)dt$. Most likely $c=\frac{1}{2\pi}=\left( \int_{-\pi}^{\pi} K_n(t)dt\right)^{-1}$ but I haven't done the calculations. –  Jose27 Sep 30 '11 at 19:15
    
I have never heard of this fact. I guess I'll just have to accept it and plough onward.... –  Kyle Schlitt Sep 30 '11 at 19:27
    
This is literally the first thing stated immediately after the definition of both the Fejer Kernel and the Cesaro mean. So I would understand that there is very little machinery available to verify this statement. –  Kyle Schlitt Sep 30 '11 at 19:44

1 Answer 1

up vote 3 down vote accepted

You simply use the fact that $\frac{1}{2 \pi} \int_{-\pi}^{\pi} K_n(t) \mathrm{d} t=1$. To see this, note the closed form expression for the Fejer kernel:

$$ K_n(t) = \frac{1}{n} \sum_{k=0}^{n-1} D_k(t) $$ where $D_k(t) = \sum_{n=-k}^{k} \exp(i t n)$. Now:

$$ \frac{1}{2\pi}\int_{-\pi}^\pi K_n(t) \mathrm{d} t = \frac{1}{2 \pi n} \int_{-\pi}^\pi \sum_{k=0}^{n-1} D_k (t) \mathrm{d} t = \frac{1}{2 \pi n} \sum_{k=0}^{n-1} \int_{-\pi}^\pi D_k (t) \mathrm{d} t = \frac{1}{2 \pi n} \sum_{k=0}^{n-1} (2 \pi) = 1 $$ where we used $\int_{-\pi}^\pi D_k (t) \mathrm{d} t = \sum_{n=-k}^{k} \int_{-\pi}^\pi {\rm e}^{i t n} \mathrm{d} t = \sum_{n=-k}^{k} ( 2\pi \delta_{n,0} ) = 2 \pi$.

share|improve this answer
    
Thank you Sasha. I literally facepalmed when I clued into the fact that $f(x)$ is independant of the variable of integration $t$. (Please forgive me I'm on cold meds today.) Of course $f(x)$ can move freely in and out of the integral. I now see why Jose27 was so brief: there really isn't much to prove. Thanks to both of you. –  Kyle Schlitt Sep 30 '11 at 20:47

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.